"Not in the business of indoctrination": religious education in South Australian public schools, 1968–1980. Issue 2 (16th October 2020) - Jackson, Stephen James
Abstract : Purpose: This paper explores religious education (RE) in South Australia from 1968–1980. It focuses especially on the collapse of the RE settlement from 1968–1972 and the controversial legislation and subsequent curricula emerging from changes to the Education Act in 1972. Design/methodology/approach: This paper draws upon archival materials, published sources from the South Australian Institute of Teachers, the South Australian Education Department and the Religious Education Project Team, as well as an interview with Malcolm McArthur, one of the most influential figures in the controversy. Findings: Following the collapse of religious instruction from 1968–1972, the Minister of Education quickly passed legislation regarding a new course of religious education. A major controversy subsequently broke out over the appropriateness and design of a new programme of religious education. Educators attempted to design an educationally sound programme of RE that would avoid the problem of indoctrination. Ultimately, a new programme was created that satisfied neither proponents nor opponents of religion in state schools, and General Religious Teaching gradually faded from South Australian classrooms by 1980. Originality/value: The article engages with broader debates on the nature of secularity in Australian history. In particular, it complicates the political-institutional approach developed by Damon Mayrl by stressing the agency and significance of elite educational and religious actors in the creation of new secular settlements. It also provides a useful addition to an older South Australian historiography by utilising newly available sources on the topic.